Performance Evaluation of a Dengue IgG Rapid Diagnostic Test Designed to Determine Dengue Serostatus as Part of Prevaccination Screening - Vasco Liberal; Remi Forrat; Cong Zhang; Charles Pan; Matthew Bonaparte; Wushan Yin; Lingyi Zheng; Valeria Viscardi; Yukun Wu; Yasemin Ataman-Önal; Stephen Savarino; Catherine Chen (Microbiology Spectrum, 2022)
ABSTRACT The World Health Organization has recommended prevaccination screening for prior dengue infection as the preferred approach prior to vaccination with the dengue vaccine CYD-TDV. These screening tests need to be highly specific and sensitive, and deliverable at the point-of-care. We evaluate here the sensitivity and specificity of the newly developed OnSite Dengue IgG rapid diagnostic test (RDT). A retrospective double-blind study of the sensitivity and specificity of the OnSite Dengue IgG RDT was performed using a sample panel consisting of archived serum specimens collected during CYD-TDV clinical trials in Latin American and Asia, with the reference serostatus for each sample determined by an algorithm using measured dengue PRNT90, PRNT50, and NS1 IgG ELISA. An additional panel of dengue seronegative samples positive for other flaviviruses and infections was used to assess cross-reactivity. Samples were included from 579 participants; 346 in the specificity panel and 233 in the sensitivity panel. The OnSite dengue IgG RDT exhibited a specificity of 98.0% (95% CI = 95.9 to 99.2) and sensitivity of 95.3% (95% CI = 91.7 to 97.6). The sensitivity for samples exhibiting a multitypic immune profile (PRNT90-positive to >1 dengue serotype) was 98.8% while for monotypic immune samples (PRNT90-positive to a single dengue serotype) it was 88.1%. The OnSite dengue IgG RDT showed minimal to no cross-reactivity to related flaviviruses. These findings support the use of the OnSite dengue IgG RDT to determine dengue serostatus in CYD-TDV prevaccination screening. IMPORTANCE Dengue remains a significant public health issue, with over 5.2 million cases reported to the World Health Organization (WHO) in 2019. The tetravalent dengue vaccine (CYD-TDV) is currently licensed for use in those aged ≥9 years; however, vaccinees with no previous exposure to dengue experience an increased risk of hospitalized and severe dengue upon subsequent heterotypic infection. Consequently, WHO recommends screening for prior dengue infection before vaccination. Screening tests for previous infection need to be highly specific and sensitive, and deliverable at the point-of-care. High sensitivity ensures that the largest number of individuals with previous infection can be identified and vaccinated, while high specificity prevents the inadvertent vaccination of those without previous infection. This study of the OnSite Dengue IgG Rapid Test, which was explicitly developed to meet this need, found that it had both high specificity (98.0% [95% CI = 95.9 to 99.2]) and sensitivity (95.3% [95% CI = 91.7 to 97.6]).